Hyper Spectral Remote Sensing of Tropical and Sub-Tropical Forest (Editors: Margaret Kalacsca & G. Arturo Sances–Publisher: Azofeita CRC Press, Year 2008, 320 pages) - I Nengah Surati Jaya (Institut Pertanian Bogor (IPB University), 2014)
It is estimated that most of the problems in forestry associated with the spatial attributes. From the perspective of forest function that includes production, ecological, and social functions, the spatial aspects has always been a very important part. In Indonesia, the forestry areas is always dealing with very large areas which is mostly inaccessible due to limitation of roads, mountainous with steep slopes, cliffs, hills or wetland such as peat, swamp or marsh. This condition makes it difficult to collect the data in quick manner comprehensively with low cost. Veronique et al. (2012) recognized that remote technology may provide objective, practical and cost-effective solution. Currently, one of the most reliable data source that can be repetitively acquired with a unique and consistent traits are those derived from satellite imageries. It had been known that since the 1990s, earth resources remote sensing sensor is progressively developed either with finer spatial resolution, higher spectral resolution, more frequent revisit or wider dynamic range. The advent of high spectral resolution (e.g. hyperspectral) is quite challenging and prospectively gives a significant contribution, especially in forest management with higher level of detailed information. Without having adequate spatial information supported by strong scientific arguments, the forestry sector will be persistently pressured by many other sectors.